Surgical Site Infections with Predominance of Multidrug Resistant in Benin: A Multicenter Study. (October 2020) - YEHOUENOU, Carine Laurence; RODRIGUEZ-VILLALOBOS, Hector; DALLEUR, Olivia; SIMON, Anne
Abstract : Background: Surgical site infections remain common and widespread; they contribute to increasing antimicrobial resistance among the etiological agents. Antimicrobial resistance is the ability of a microorganism like bacteria to stop an antimicrobial from working against it. This study was conducted to determine the spectrum of bacterial isolates from surgical site infections and their susceptibility patterns. A secondary outcome was to compare bacterial identification by a local lab and a European one. Methods: This descriptive cross-sectional study was conducted between January and August 2019 in 6 public hospitals in Benin. Pus specimens were processed using standard microbiological procedures, and identification was performed using the analytical profile index (API). Antimicrobial susceptibility testing was performed in Benin following the modified Kirby-Bauer disk-diffusion technique and was confirmed in Belgium by MALDI-TOF mass spectrometry. A second antimicrobial susceptibility test was performed using BD Phoenix automated microbiology system (Becton Dickinson). Clinical data of enrolled patients were obtained from hospital records. Results: The mean age of patients was 32 ± 11 years (range, 18–76). The median time for surgical site infections was 9 postoperative days. Of the 229 patients from whom wound swabs were collected, 195 (85.15%) showed positive aerobic bacterial growth. In total, 164 pathogenic bacteria were isolated, including 41 gram-positive organisms (25%), 78 gram-negative fermentative bacteria (47.5%), and 45 gram-negative nonfermentative bacteria (27.5%). We observed 3 discrepancies between API technique and MALDI-TOF. Two Klebsiella pneumoniae and 1 Pseudomonas spp (API) versus, respectively, Klebsiella varicola and Pseudomonas mendocina (MALDI-TOF). The most prevalent bacterial species were E. coli (31%), followed by S. aureus (25%), Pseudomonas aeruginosa (18%), and Klebsiella pneumoniae (11%). Of the 41 S. aureus, 26 (63, 41%) were methicillin-resistant Staphylococcus aureus (MRSA), and 3 of these were carrying both MRSA and induced clindamycin resistance (ICR). Extended-spectrum β-lactamase (ESBL)–producing Enterobacteriaceae were observed in 60 of 78 isolates tested (77%). All of 2 Morganella morgannii and 89% of K. pneumoniae were ESBL producers. Conclusions: Among S. aureus, 2 of 3 were MRSA, whereas almost K. pneumoniae and E. coli were ESBL producers. Three strains are pan–drug resistant in nonfermentative bacteria, and no isolate was susceptible to all antibiotics. These findings are of high interest for better management of patients and control of antimicrobial resistance in Benin. Funding: This study was supported by Académie de Recherche pour l'Enseignement Supérieur (ARES). Disclosures: None